Rett Syndrome. A Case Presentation - Julio Padrón González; Ramón Pérez Mejías; Lidys Padrón Fernández; Leydis Padrón Fernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Rett syndrome is a neurological disorder of genetic basis. It affects almost exclusively girls and women being the estimated incidence of this disease in the general population of one case per 10,000 women. In its classical type it is of one in every 15. 000 births. Its diagnosis is descriptive, based on a set of signs and symptoms, but not etiologic. Treatment is symptomatic and supportive. Rett syndrome is frequently misdiagnosed as autism or cerebral palsy. It should be suspected in female patients, diagnosed with child cerebral palsy or idiomatic mental retardation, supported by internationally established criteria. The case of an 11 years old girl visited at her home and attended by doctors of the Barrio Adentro mission in the Bolivarian Republic of Venezuela is presented. The patient was normal until about two years old when she began presenting impairment of psychomotor skills, social and behavioral disorders with infantile autism traits, seizures and considerable mental retardation.